A Discrete-Ordinate Discontinuous-Streamline Diffusion Method for the Radiative Transfer Equation (Communications in Computational Physics, 2020)
The radiative transfer equation (RTE) arises in many different areas of scienceand engineering. In this paper, we propose and investigate a discrete-ordinatediscontinuous-streamline diffusion (DODSD) method for solving the RTE, which is acombination of the discrete-ordinate technique and the discontinuous-streamline diffusionmethod. Different from the discrete-ordinate discontinuous Galerkin (DODG)method for the RTE, an artificial diffusion parameter is added to the test functions inthe spatial discretization. Stability and error estimates in certain norms are proved.Numerical results show that the proposed method can lead to a more accurate approximationin comparison with the DODG method.